ESTABLISHING ANTI-LEPTOSPIRA CADRES SUPPLIED BY PERSUASIVE COMMUNICATION, CLEAN & HEALTHY BEHAVIOR KITS, AND POCKET BOOKS FOR PREVENTING LEPTOSPIROSIS - Noviana Dewi; Muhammad Taufiq Qurrohman; Vina Dwi Kusuma Putri; Virsa Nadya Yulieta; Vive Budi Cahyani; Wijayanti Arum Pradita; Willia Jeany Valentine; Winda Rahmadani (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
The purpose of this counseling is to increase public knowledge about the Clean and Healthy Lifestyle (PHBS) as an effort to prevent the spread of leptospirosis and to determine the risk factors for leptospirosis.This extension method is by giving pres-test and post-test questions to the extension participants, then the results of these scores are tested by using the Paired Sample Test. Changes as indicated by the significance value (2-tailed) on the knowledge questionnaire about leptospirosis was 0.000 which showed a significant difference.From this outreach activity, it was concluded that the material about leptospirosis could be well understood by looking at the increase in scores on the pre-test and post-test. From the satisfaction questionnaire filled out by all participants, the results obtained in the satisfactory category. In addition, the counseling participants were also active in sharing knowledge about efforts to prevent the spread of leptospirosis to other communities.